Shared Leadership and Organizational Performance in DKI Jakarta - Abdullah, Putri Allana; Juhary, Ali (2023)
The purpose of this study is to describe how leadership shares in improving organizational performance. The research method uses a quantitative approach. Data were collected from respondents, totaling 120 employees who served at the DKI Jakarta Tourism Office. The 120 respondents were taken from a total population of 668 employees using the Slovin formula with simple random sampling technique. The results of the study indicate that shared leadership is reflected by establishing teamwork; conduct training and system development; provide rewards to employees; build a strong work culture; build communication; directing subordinates to commitment has been able to improve organizational performance well.